Anti-inflmatory Activity Test of Ethanol Extract of Betel Leaves Green (Piper betle L.) Against White Male Rats Carrageenan Induced - Meilinda EkaFujiyanti; Sholihatil Hidayati; Dhina Susanti (LPPM Universitas dr. Soebandi, 2024)
Background: Inflammation is an attempt by the body to eliminate invading organisms, preparation for tissue preparation, and to eliminate irritants. The use of anti-inflammatory drugs can reduce the symptoms of inflammation. One of the natural ingredients as an alternative treatment that can be used as an anti-inflammatory is green betel leaves (Piper betle L.). Purpose: To determine the most effective dose (100, 200, and 400 mg/kgBB) of green betel leaf ethanol extract (EEDSH) as an anti-inflammatory based on the volume of edema in the feet of white male rats induced by carrageenan. Methods : The extract was made by maceration method using 70% ethanol solvent. The research used was a laboratory experiment using white male rats as test animals divided into 5 groups, namely negative control (CMC Na), positive control (Sodium Diclofenac), EEDSH treatment group with doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/KgBW with 1% carrageenan induction. Anti-inflammatory activity was analyzed by % anti- inflammatory power calculated based on measurements of edema volume. Analysis of research data using SPSS 25 using One Way ANOVA (p <0.05). Results: The results of the percentage of anti-inflammatory power of positive control, EEDSH doses of 100 mg/KgBB, 200 mg/KgBB, and 400 mg/KgBB were 29.13%, 31.43%, 32.66%, 31.45%. The results of statistical testing obtained a value of 0.366 (P>0.05) which means there is no significant difference. Conclusions: Ethanol extract of green betel leaves has anti-inflammatory activity against white male rats induced by carrageenan with the most effective dose being a dose of 100 mg/KgBW which has an anti-inflammatory effect that is not significantly different from the positive control